2011
DOI: 10.1074/jbc.m111.274159
|View full text |Cite
|
Sign up to set email alerts
|

Human Mre11/Human Rad50/Nbs1 and DNA Ligase IIIα/XRCC1 Protein Complexes Act Together in an Alternative Nonhomologous End Joining Pathway

Abstract: Recent studies have implicated a poorly defined alternative pathway of nonhomologous end joining (alt-NHEJ) in the generation of large deletions and chromosomal translocations that are frequently observed in cancer cells. Here, we describe an interaction between two factors, hMre11/hRad50/Nbs1 (MRN) and DNA ligase III␣/XRCC1, that have been linked with alt-NHEJ. Expression of DNA ligase III␣ and the association between MRN and DNA ligase III␣/XRCC1 are altered in cell lines defective in the major NHEJ pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 66 publications
(71 reference statements)
4
107
0
Order By: Relevance
“…7, A and C). This result is unexpected because MRX promotes Ku-mediated end joining in budding yeast (41), and a previous study showed that MRN strongly stimulates DNA ligation by DNA ligase III-XRCC1 by mediating DNA end tethering in vitro (50). It is possible that human MRN-mediated end synapsis promotes the activity of ligase III-XRCC1 but does not provide a configuration of ends that is favorable for the ligase IV-XRCC4 complex.…”
Section: Discussionmentioning
confidence: 92%
“…7, A and C). This result is unexpected because MRX promotes Ku-mediated end joining in budding yeast (41), and a previous study showed that MRN strongly stimulates DNA ligation by DNA ligase III-XRCC1 by mediating DNA end tethering in vitro (50). It is possible that human MRN-mediated end synapsis promotes the activity of ligase III-XRCC1 but does not provide a configuration of ends that is favorable for the ligase IV-XRCC4 complex.…”
Section: Discussionmentioning
confidence: 92%
“…It was hypothesized that cells deficient in XRCC4, a factor involved in classical NHEJ, would use the alt-NHEJ pathway for DSB repair; however, depletion of MRE11 markedly decreased alt-NHEJ, suggesting a role of MRE11 in this alternative pathway, most likely when it is in the form of the MRN complex (Dinkelmann et al, 2009;Rass et al, 2009). DNA ligase IIIα and XRCC1 were also reported to be involved in the alt-NHEJ pathway (Della-Maria et al, 2011). The MRN complex has been confirmed to interact with the DNA ligase IIIα/XRCC1 complex directly and to stimulate DNA ligase IIIα/XRCC1-dependent intermolecular ligation in vitro, even for incompatible DNA ends, which mirrors alt-NHEJ repair, suggesting that NBS1 and likely the MRN complex participate in the alt-NHEJ pathway.…”
Section: Introductionmentioning
confidence: 99%
“…XRCC1 is a DNA repair factor that has recently been implicated as a component of A-EJ (17,18). Because XRCC1 is essential for mouse embryonic development (20), there is a lack of direct genetic evidence for its involvement in CSR and A-EJ.…”
Section: Resultsmentioning
confidence: 99%
“…XRCC1 was recently implicated as a component of A-EJ (17,18). If that were the case, deletion of Xrcc1 in NHEJ-deficient cells (e.g., Lig4 Δ/Δ ) should inhibit CSR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation